Function-reconfigurable water short backfire antenna - Ren, Zhen (2021)
A novel short backfire antenna realized by replacing the metallic wall with water wall is described in this paper. Through controlling the water flow in different layers, the proposed short backfire antenna based on a cylindrical waveguide made of water can switch between two different functions. When the proposed antenna works in Function I, it is a short backfire antenna with pencil beam. When it operates in the other function, conical beam is achieved, and its beam angle can be changed by controlling the height of water cylinder and water wall. Measured results show that when working in Function I, the proposed water short backfire antenna has an impedance bandwidth (|S11| <; -10 dB) of 11.3% (3.6 GHz to 4.05 GHz). A maximum gain of 10.8 dBi is observed. While working in Function II, the beam angle of a conical radiation beam can be switched between 25° and 60°. The operating frequency of the antenna working in Function II covers a range of 5% (3.9 GHz to 4.1 GHz). Maximum gain of 6.8 dBi for 25° and 2.7 dBi for 60° is obtained. Due to its low cost, good radiation performances, transparent characteristic, and reconfigurability, this novel water antenna may be potentially useful in future communication applications.